Parent-of-origin effects on seed development in Arabidopsis thaliana require DNA methylation. - Adams, S; Vinkenoog, R; Spielman, M; Dickinson, H; Scott, R (2000)
Some genes in mammals and flowering plants are subject to parental imprinting, a process by which differential epigenetic marks are imposed on male and female gametes so that one set of alleles is silenced on chromosomes contributed by the mother while another is silenced on paternal chromosomes. Therefore, each genome contributes a different set of active alleles to the offspring, which develop abnormally if the parental genome balance is disturbed. In Arabidopsis, seeds inheriting extra maternal genomes show distinctive phenotypes such as low weight and inhibition of mitosis in the endosperm, while extra paternal genomes result in reciprocal phenotypes such as high weight and endosperm overproliferation. DNA methylation is known to be an essential component of the parental imprinting mechanism in mammals, but there is less evidence for this in plants. For the present study, seed development was examined in crosses using a transgenic Arabidopsis line with reduced DNA methylation. Crosses between hypomethylated and wild-type diploid plants produced similar seed phenotypes to crosses between plants with normal methylation but different ploidies. This is consistent with a model in which hypomethylation of one parental genome prevents silencing of alleles that would normally be active only when inherited from the other parent - thus phenocopying the effects of extra genomes. These results suggest an important role for methylation in parent-of-origin effects, and by inference parental imprinting, in plants. The phenotype of biparentally hypomethylated seeds is less extreme than the reciprocal phenotypes of uniparentally hypomethylated seeds. The observation that development is less severely affected if gametes of both sexes (rather than just one) are 'neutralized' with respect to parent-of-origin effects supports the hypothesis that parental imprinting is not necessary to regulate development.